A randomised comparison of three different immobilisation devices for thoracic and abdominal cancers. Issue 2 (20th December 2016) - Hubie, Catherine; Shaw, Maddison; Bydder, Sean; Lane, Jonny; Waters, Gemma; McNabb, Megan; Kearvell, Rachel; Concannon, Alicia; Bharat, Chrianna; Appleyard, Rob
Abstract: Introduction: Patient immobilisation is critically important for both highly conformal conventionally fractionated radiotherapy and for stereotactic body radiotherapy. Different immobilisation devices are available to maintain patient position for radiotherapy but the most suitable one remains unknown. Methods: Forty‐five patients were randomly allocated to one of three immobilisation devices; the Q fix arm shuttle, BodyFIX without wrap or BodyFIX with wrap. Patients were imaged before and after treatment to ascertain intra‐fraction and inter‐fraction motion. Bony anatomy was used for matching to determine the positional accuracy of each device. Treatments were timed using a standard method. Patient comfort and staff satisfaction questionnaires were also issued to determine comfort, ease of use and preferences for each device. Results: The BodyFIX without wrap was the more accurate device; however, the differences between the devices were not statistically significant. The BodyFIX with wrap was found to take significantly longer to set up and set down compared to the arm shuttle and the BodyFIX without wrap (all P < 0.001). Patients (37%) marginally preferred the BodyFIX with wrap. Most (81%) staff preferred the BodyFIX without wrap. Conclusion: Immobilisation using the BodyFIX without wrap was deemed to be suitable for clinical use. It was a clinically accurate device, the more efficient in terms of set up and set down time, the most preferred by staff and was accepted by patients. Abstract : A randomised comparison of three different immobilisation devices for thoracic and abdominal cancers, to determine the most accurate device for patient positioning; most efficient for treatment and the device most tolerated by patients.